Succession Characteristics of Soil Microbial Communities Along Elevational Gradients in the Lhasa River Basin and Analysis of Environmental Driving Factors - Xiaoyu Li; Xiangyang Sun; Baosheng An; Suyan Li; Jiule Li; Chuanfei Wang (Microbiology Research, 2025)
The Qinghai-Xizang Plateau is among the most ecologically vulnerable and responsive areas worldwide. Studying the characteristics of soil microbial communities along altitudinal gradients on plateaus and revealing the response mechanisms and vertical distribution patterns of microbial communities in alpine ecosystems is of significant academic value for assessing the ecological stability of the Qinghai-Xizang Plateau. This research examines the Lhasa River Basin by employing Illumina NovaSeq high-throughput sequencing to investigate how soil bacterial and fungal communities shift across elevation gradients in the Duilong Qu subbasin. This study also explored the key environmental drivers behind these microbial distribution patterns. The results indicate the following: (1) Key bacterial groups in the Duilong Qu Basin soil include Proteobacteria, Acidobacteria, and Actinobacteria, with Ascomycota, Mortierellomycota, and Basidiomycota as the prevalent fungal phyla. (2) Soil bacterial richness fluctuates with increasing elevation, and diversity exhibits a V-shaped distribution; fungal richness increases monotonically with elevation, whereas diversity shows no altitudinal dependence. (3) Principal coordinate analysis (PCoA) revealed that bacterial community structures exhibit separation trends across different elevations, with high intragroup consistency; fungal community structures at mid-elevations (4000–5000 m) show clustering similarity, whereas those at 3650–5000 m and 5500 m remain highly distinct from those at other elevations. (4) RDA reveals that factors such as accessible phosphorus, potassium, and organic content have a major effect on how bacterial communities are arranged. On the other hand, soil conductivity, along with available and total phosphorus levels, as well as pH, plays a key role in shaping fungal communities. (5) Functional prediction analysis suggests that soil bacteria shift from aerobic and biofilm-forming to facultatively anaerobic, stress-tolerant, and pathogenic traits with increasing elevation. Fungi are predominantly undefined saprotrophs, transitioning from ectomycorrhizal and pathogenic functions to saprotrophic functions at relatively high elevations.